2018
DOI: 10.1530/ec-17-0309
|View full text |Cite
|
Sign up to set email alerts
|

Exogenous insulin antibody syndrome (EIAS): a clinical syndrome associated with insulin antibodies induced by exogenous insulin in diabetic patients

Abstract: Insulin has been used for diabetes therapy and has achieved significant therapeutic effect. In recent years, the use of purified and recombinant human insulin preparations has markedly reduced, but not completely suppressed, the incidence of insulin antibodies (IAs). IAs induced by exogenous insulin in diabetic patients is associated with clinical events, which is named exogenous insulin antibody syndrome (EIAS). The present review is based on our research and summarizes the characterization of IAs, the factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
68
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 71 publications
1
68
1
Order By: Relevance
“…Studies suggested that the development of IAA might not interfere with insulin action. 21 However, variable degrees of hypoglycemia might be associated with IAA. 22 Hypoglycemia is known to be the pitfall that limits the intensification of insulin therapy, making it difficult for a clinician to achieve optimal glycemic control.…”
mentioning
confidence: 99%
“…Studies suggested that the development of IAA might not interfere with insulin action. 21 However, variable degrees of hypoglycemia might be associated with IAA. 22 Hypoglycemia is known to be the pitfall that limits the intensification of insulin therapy, making it difficult for a clinician to achieve optimal glycemic control.…”
mentioning
confidence: 99%
“…Use of purified and recombinant human insulin corresponds with reduced incidence of EIAS . Switching insulin formulations can ameliorate complications, as can smaller meals with slowly absorbable carbohydrates .…”
Section: Discussionmentioning
confidence: 99%
“…Anti‐insulin antibody formation is a rare cause of hyperinsulinemic hypoglycemia. Previously described in autoimmune form among insulin‐naïve patients, cases occur in diabetics treated with exogenous insulin, prompting the term “exogenous insulin antibody syndrome”(EIAS) . While EIAS treatment is not discussed in the American Society for Apheresis (ASFA) guidelines, therapeutic plasma exchange (TPE) has been documented in case reports as an effective treatment .…”
Section: Introductionmentioning
confidence: 99%
“…Insulin antibody syndrome is characterized by episodes of hyper-insulinemic hypoglycemia that occur most often post-prandially, although fasting and exercise induced hypoglycemia has been described. In Japan, association has been seen with other autoimmune diseases in 96% cases (Graves' disease, Rheumatoid arthritis) (2,3). After a meal, there is initial hyperglycemia followed by hypoglycemia a few hours later.…”
Section: Case Reportmentioning
confidence: 99%